NANOCOMPOSITІON FOR TREATMENT OF CHRONIC APICAL PERIODONTITIS AND BONE REPAIR - Shevchenko, V.K.; Melnyk, V.L.; Kostyrenko, O.P.; Sylenko, B.Yu.; Sylenko, Yu.I. (World of Medicine and Biology, 2026)
This paper presents a clinical case of diagnosing the density of the alveolar bone of the mandible and its architectonics in a patient with chronic apical periodontitis. The density of the alveolar bone of the mandible was determined in the periapical areas of the affected teeth. The results were evaluated in Hounsfield units using the classification of bone tissue types by C. E. Misch. The clinical study evaluated the effectiveness of treating chronic apical periodontitis with a phosphate buffer using the proposed method. The article describes the mechanism of action of this composition, which stimulates bone mineralization and promotes the restoration of mineralized bone tissue structures. As a result of the chemical reactions between the two reagents, a nanocomposite structure forms. In 85.2 % of treatment cases, a positive result was obtained. We carried out the specified diagnostic algorithm for the individualized treatment of chronic apical periodontitis. Analysis of the obtained results (change in density from D4 to D3) indicates the effectiveness of phosphate buffer in the apical region of the periodontium. In further studies, it is planned to continue studying the density of bone tissue of the periapical structures of the upper jaw.
Keywords: bone repair; chronic apical periodontitis; calcium chloride; phosphate buffer